Mental health, family orientation, and individualism: a systematic review and meta-analysis in Iranian students. Issue 5 (13th November 2017) - Mostafavi, Hakimeh; Ziloochi, Mohammad Hossein; Delavari, Sajad; Rezaei, Satar; Homaie Rad, Enayatollah
Abstract : Purpose: Mental health is one of the most important factors for evaluating the health of different age groups in the community. The most common forms of mental health disorders are depression and anxiety. Health status of students as an important age group has positive consequences in the community. To provide special recommendations for preventing mental disorders, the purpose of this paper is to determine the correlations among the individualism and family orientation and mental health. Design/methodology/approach: A meta-analysis was conducted to find scores of mental health. International databases of Scopus and PubMed as well as Iranian databases of IranMedex and SID were systematically searched in September 2014 for studies conducted on Iranian students. Of 379 reviewed studies, 58 were selected for meta-analysis. A meta-regression model was estimated to show the effects of individualism and family orientation on mental health. Findings: Eight studies were conducted in Tehran. Eight studies were published in English. In nine studies, school students, and in one study both school and university students were surveyed. General Health Questionnaire-28 score varied from 13.77 in Arak to 47.78 in Tehran. The results of this study showed that the pooled mental health score for Iranian students was 23.725, indicating that Iranian students had poor mental health. In meta-regression, the coefficient of family orientation was −0.2893 and it was significant. Other variables did not have any significant relationship with mental health scores. Originality/value: Improvement of living conditions and enabling the youth to positively communicate with different social groups are recommended.